Miejsce innowacji w klastrach przedsiębiorstw - Pohulak-Żołędowska, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Cluster structures differ depending on in which developed economies they are located. Developing countries can obtain clusters, but these are much shallow and worse organized than those existing in well-developed economies. What distinguishes those entities is also their attitude to creating innovation. Innovation does not have to be necessary linked to high-technology. The process innovation or design are also the types of innovation. That is why both traditional and science-based clusters can be innovative ones. The key point here is that depending on location of the cluster (whether it is well-developed or developing economy) the innovation might be a result of close co-operation between firms and consumers (in well-developed economies) or a country's economic policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 464-472